The Role of Technological Media in the Character Building Education Process for Generation Z: A Literature Review - Shinta Shinta; Muh. Azhar; Partino Partino; Fitriah M. Suud (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine various technology-based media used in the world of education to shape character for Generation Z Research design and method should be clearly defined. The method in this research is a literature review of various research studies published in Scopus-indexed journals. This is the basis for researchers to choose general keywords, namely "technology media," "Generation Z," and " character education. " These keywords are then used to obtain internal literature data from the Scopus database. The search was carried out in the period 2010 – 2024.The search results obtained 57 metadata, including titles and abstract and analysis was carried out with the help of VOSviewer to find patterns of interrelationship between studies. The result showed learning media, character and character education, and Generation Z began to be discussed in 2020, so research discussing this can still be said to be new research. The visualization image above shows that most of the research that has been carried out discusses students and education. In contrast, more research needs to be carried out regarding learning media. Research on character education and Generation Z is also based on the above visualizations, which previous researchers have yet to carry out much. Based on the research that has been conducted, it can be seen about several benefits from using technology-based learning media, such as AR Alphabet Book, Game Animation Software, Whiteboard Animation Video, Visual Based Learning, Social MediaVideo Games, Visual Game Character Design Digital Anti-Corruption, Interactive Teaching Physics Materials, and E-Assessment